Repriming by PrimPol is critical for DNA replication restart downstream of lesions and chain-terminating nucleosides. Issue 15 (2nd August 2016) - Kobayashi, Kaori; Guilliam, Thomas A.; Tsuda, Masataka; Yamamoto, Junpei; Bailey, Laura J.; Iwai, Shigenori; Takeda, Shunichi; Doherty, Aidan J.; Hirota, Kouji
ABSTRACT: PrimPol is a DNA damage tolerance enzyme possessing both translesion synthesis (TLS) and primase activities. To uncover its potential role in TLS-mediated IgVλ hypermutation and define its interplay with other TLS polymerases, PrimPol −/− and PrimPol −/− /Pol η −/− /Pol ζ −/− gene knockouts were generated in avian cells. Loss of PrimPol had no significant impact on the rate of hypermutation or the mutation spectrum of IgVλ . However, PrimPol −/− cells were sensitive to methylmethane sulfonate, suggesting that it may bypass abasic sites at the IgVλ segment by repriming DNA synthesis downstream of these sites. PrimPol −/− cells were also sensitive to cisplatin and hydroxyurea, indicating that it assists in maintaining / restarting replication at a variety of lesions. To accurately measure the relative contribution of the TLS and primase activities, we examined DNA damage sensitivity in PrimPol −/− cells complemented with polymerase or primase-deficient PrimPol. Polymerase-defective, but not primase-deficient, PrimPol suppresses the hypersensitivity of PrimPol −/− cells. This indicates that its primase, rather than TLS activity, is pivotal for DNA damage tolerance. Loss of TLS polymerases, Polη and Polζ has an additive effect on the sensitivity of PrimPol −/− cells. Moreover, we found that PrimPol and Polη-Polζ redundantly prevented cell death and facilitated unperturbed cell cycle progression. PrimPol −/− cells also exhibited increased sensitivity to a wide variety of chain-terminating nucleoside analogs (CTNAs). PrimPol could perform close-coupled repriming downstream of CTNAs and oxidative damage in vitro . Together, these results indicate that PrimPol's repriming activity plays a central role in reinitiating replication downstream from CTNAs and other specific DNA lesions.